2017
DOI: 10.18203/2320-1770.ijrcog20175298
|View full text |Cite
|
Sign up to set email alerts
|

Novel use of balloon tamponade saves a patient with uterine inversion in severe shock

Abstract: A patient with G1P0 status 38 weeks pregnancy with pain with no high risk delivered at PHC, Hatod, Madhya Pradesh (India). She delivered a male baby by spontaneous vaginal delivery of 3.1 kg. All of sudden after 2nd stage of labour, her 3rd stage of labour was eventful. Placenta did not come out spontaneously so controlled cord traction was given by the ANM over the PHC. She was given intramuscular oxytocin 5 IU. She did the traction with proper care but inspite of that while doing so placenta got separated bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…The placenta did not come out spontaneously so controlled cord traction was performed. The doctor performed the traction carefully but there was a complete inversion of the uterus [14] . An accurate diagnosis needs to be made early because there is a misdiagnosis between uterine prolapse and uterine inversion.…”
Section: Discussionmentioning
confidence: 99%
“…The placenta did not come out spontaneously so controlled cord traction was performed. The doctor performed the traction carefully but there was a complete inversion of the uterus [14] . An accurate diagnosis needs to be made early because there is a misdiagnosis between uterine prolapse and uterine inversion.…”
Section: Discussionmentioning
confidence: 99%
“…10 In another study by Yadav et al Bakri balloon was used effectively in cases of uterine inversion with fewer complications (infection and necrosis uterine) compared to uterine sutures. 11 Bakri balloon not only helps for uterine atony, it is also a re-inversion prevention method. Vivanti et al, were successful in using Bakri Balloon in the treatment of puerperal uterine inversion during caesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Yadav S et al, also reported the effectiveness of balloon tamponade in patient with uterine inversion. 8 In two patients of atonic bleeding B Lynch uterine compressive sutures were applied simultaneously with balloon tamponade. Wai Yoong et al, also reported the successful application of uterine compression suture in association with intrauterine balloon tamponade (uterine sandwitch).…”
Section: Discussionmentioning
confidence: 99%